Ethnomathematical exploration: Mathematical concepts in the Kolong pigeon game - Eka Zuliana; Femas Anggit Wahyu Nugroho (Journal of Honai Math, 2025)
Ethnomathematics, as an interdisciplinary field, emphasizes the fundamental integration of mathematics with cultural practices and knowledge systems. Indonesia's multicultural context provides exceptional opportunities for ethnomathematical investigation, particularly within the domain of culturally embedded games and recreational practices. This study examines the mathematical concepts embedded within the Kolong pigeon game, a traditional cultural practice documented during a regional Kolong pigeon competition held in Gondoharum, Kudus, Jawa Tengah, Indonesia. Employing a qualitative research design grounded in realist ethnographic methodology, data were collected through structured interviews, systematic observation, and comprehensive documentation. Data validity was established through triangulation techniques, cross-referencing findings from interviews, observational field notes, and documentary evidence. Data analysis followed a qualitative analytical framework consistent with Cresswell's approach to qualitative data interpretation. The findings reveal that the Kolong pigeon game demonstrates extensive utilization of geometric concepts, particularly two-dimensional and three-dimensional spatial representations within the game arena. These include explicit applications of symmetry, rectangular and square configurations, cubic and cylindrical shapes. Additionally, the study identified significant implementation of angular concepts within the formal rules governing players' body positioning and spatial orientation. These findings advance ethnomathematical scholarship by illuminating mathematical structures within culturally contextualized games and provide empirically grounded resources for pedagogical integration of cultural games into mathematics instruction.